Pengaruh Kualitas Kehidupan Kerja terhadap Intensi Turnover Karyawan Hotel Bintang Tiga - Alfiyah, Hilmy Aulia; Widawati, Lisa; Utami, Ayu Tuty (Bandung Conference Series: Psychology Science, 2024)
Abstract. The hospitality industry in Indonesia is a rapidly growing economic sector and has an important role in supporting tourism and the national economy. Where in this development is accompanied by a high turnover intention in Indonesia, especially for employees who work in the hospitality industry in the hospitality sector. One of the factors that encourage hotel employees to change workplaces is the perception that the quality of their work life has not been fulfilled properly. The purpose of this study is to see the extent of the influence of quality of work life on turnover intention in hotel employees. This study used a non-experimental quantitative method, involving 98 respondents and applying a simple regression analysis test. The measuring instrument for the quality of work life variable was adapted by Wardani (2019), which refers to Walton's (1973) measuring instrument. While the measuring instrument for the turnover intention variable was adapted by Tata Saefullah (2019), which refers to Mobley's (1978) measuring instrument. The results of simple regression analysis show that quality of work life is significantly correlated to turnover intention. This correlation is indicated by the negative regression coefficient (quality of work life = -0.069), which shows that the higher the quality of work life, the lower the turnover intention. In addition, the coefficient of determination reveals that 16.2% of the turnover intention variable is influenced by the variables in quality of work life. Abstrak. Industri perhotelan di Indonesia adalah sektor ekonomi yang berkembang pesat dan memiliki peran penting dalam mendukung pariwisata dan ekonomi nasional. Dimana dalam perkembangan ini disertai adanya intensi turnover yang tinggi di Indonesia, terutama pada karyawan yang bekerja di industri hospitality bidang perhotelan. Salah satu faktor yang mendorong karyawan hotel untuk berpindah-pindah tempat kerja adalah persepsi bahwa kualitas kehidupan kerjanya belum terpenuhi dengan baik. Tujuan dari penelitian ini adalah untuk melihat sejauh mana pengaruh kualitas kehidupan kerja terhadap intensi turnover pada karyawan hotel. Penelitian ini menggunakan metode kuantitatif non-eksperimental, dengan melibatkan 98 responden dan menerapkan uji analisis regresi sederhana. Alat ukur untuk variabel kualitas kehidupan kerja diadaptasi oleh Wardani (2019), yang merujuk pada alat ukur Walton (1973). Sementara alat ukur untuk variabel intensi turnover, diadaptasi oleh Tata Saefullah (2019), yang merujuk pada alat ukur Mobley (1978). Hasil analisis regresi sederhana menunjukkan bahwa kualitas kehidupan kerja berkorelasi signifikan terhadap intensi turnover. Korelasi ini ditunjukkan oleh nilai koefisien regresi bertanda negatif (kualitas kehidupan kerja = -0.069), yang memperlihatkan semakin tinggi kualitas kehidupan kerja maka semakin rendah intensi turnover. Selain itu, koefisien determinasi mengungkapkan bahwa sebesar 16.2% dari variabel intensi turnover dipengaruhi oleh variabel dalam kualitas kehidupan kerja.